Saphenous Artery Perforator Flaps in Minipigs: Anatomical Study and a New Experimental Model. Issue 5 (28th May 2021) - Zhan, Yi; Zhu, Hongzhang; Li, Wenwen; Su, Qiao; Liu, Xiao-Lin; Qi, Jian
Abstract: This study describes the anatomy of the saphenous artery (SA) perforators in minipigs and the development of a new animal model. First, the anatomic characteristics of the SA and perforators in minipigs were examined after latex-lead oxide perfusion. Subsequently, the right hind limbs of 10 minipigs were used to generate capillary perforator flaps (group A; utilizing the SA and 5.5 cm of deep fascia above the knee), while all perforators of the left hind limbs were reserved (group B). Four additional minipigs were used to evaluate SA perforator flaps with capillary perforators plus sarcolemma and a small amount of muscle (group C). Preoperative and postoperative CTA of both hind limbs confirmed that all perforators were ligated in groups A and C. The average length of the SA was 14.86 ± 0.76 mm. The diameters of the SA at initiation, the medial tibial condyle, and the medial malleolus were 1.73 ± 0.15 mm, 1.50 ± 0.12 mm, and 1.30 ± 0.13 mm, respectively. There were 7.09 ± 1.16 perforators per hind limb, with an average diameter of 0.40 ± 0.13 mm (range, 0.10–0.78 mm), and the majority (96.2%) had a diameter >0.2 mm. The survival rates of the flaps in groups A, B, and C were 32 ± 39%, 100%, and 60.2 ± 17%, respectively. The position of the SA in minipigs is constant, its diameter is relatively large, and it has many perforators, allowing it to be used as a reliable model of perforator flaps, including capillary perforator flaps.